Improved chemical treatment of Sušica surface water, Zlatibor area, and sludge application - Cvijović, Mirjana; Murić, Milorad; Čudić, Vladica (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose: Sušica source surface water varies in natural organic and inorganic impurities, biological species and micro-organisms. This water is used instead of Vrutci lake water that has been stronglly affected by eutrophication. These waters need removal of pollutants with coagulants and polyelectrolyte. The aim of research was to improve the surface water treatment (coagulation and flocculation), to reduce sludge amount and to evaluate its quality, treatment and application. Methods: The physical-chemical methods are developed for determining the quality parameters of water, sludge and compost. These parameters are: turbidity, KMnO4 consumption, metals, total organic carbon, total nitrogen, and chlorophyll. Results: Surface water quality has a strong impact on sludge. The concentrations of metals in the sludge were: 72200 mgkg-1 Al, 8550 mgkg-1 Fe, and 106 mgkg-1 Zn. The metals over the maximum limit were: Ni 169 mgkg-1, Cr 69.5 mgkg-1, Pb 5.7 mgkg-1, and they have to be reduced by zeolite. The „nutrients” concentrations were: 697 mgkg-1 P, 297 mgkg-1 K, 9.6 mgkg-1 total N, and 274 mgkg-1 of dissolved organic carbon. Escherichia coli and Salamonella are important for converting sludge to compost. Conclusions: After maturation, compost can be used for Coriandrum sativum cultivation. In further work, this strategy should be applied to the water and sludge from Vrutci lake.